"Revoada" a reinterpretation of Bel Borba: Geographing in the country school through mosaic art - Santos , Laiany Rose Souza; Carvalho , Diana Mendonça de; Santos, Maria Daniele Oliveira dos (Seven Editora, 2024)
The article presents the result of the extension project "Revoada – a rereading of Bel Borba", using art as a way of geographizing, as a possible policy for the democratization of space. The objective was to develop geographical knowledge through the construction of a mosaic panel at the Prefeito João Alves dos Santos Agricultural School, based on the geographical formation of production and appropriation of space from the reinterpretation of the mosaic street work of Bel Borba known as Pássaros. To this end, we use bibliographic studies, documentary analysis on the impact of street works, participation of the social subjects that make up the school community in geographical pedagogical workshops, with themes from art in the city and in the countryside, mosaic workshops and installation of mosaics produced at the Agricultural Technical School Mayor João Alves dos Santos, Itabaiana/SE, which resulted in the launch of the work "REVOADA: A Rereading of Bel Borba". As a result, we point out the need to think about the local space, since our actions have driven in the students in training of the geography course a new thinking of the geographical space and the possibility of recreating it, modifying it, as well as contributing to the students of the school unit in the consolidation of knowledge and reconstruction of their living space. DOI:https://doi.org/10.56238/sevened2024.009-019